Angiosperm diversity of Lawachara National Park (Bangladesh): a preliminary assessment - Uddin, Mohammad Zashim; Hassan, Md. Abul (Bangladesh Journal of Plant Taxonomy, 2010)
<span style="font-family: "Times New Roman"; font-size: 9pt; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-family: "Times New Roman";">The present article focuses on an inventory of angiosperm diversity of Lawachara National Park. Using traditional taxonomic techniques data have been collected from the park during January to October 2008. In this preliminary assessment, a total of 374 angiosperm species including cultivated ones have been catalogued under 84 families. Nineteen threatened plant species have also been recognized in the park. Keywords: Preliminary assessment; angiosperm diversity; Lawachara National Park. DOI: 10.3329/bjpt.v17i1.5387 Bangladesh J. Plant Taxon. 17(1): 9-22, 2010 (June)